2011
DOI: 10.1364/oe.19.022462
|View full text |Cite
|
Sign up to set email alerts
|

One-step integration of metal nanoparticle in photonic crystal nanobeam cavity

Abstract: A single step process of integrating a resonantly tuned silver nanoparticle into photonic crystal nanobeam cavities fabricated by focused ion beam milling is presented. Even though the quality factor of the cavities is reduced by a factor of 20, the emission peak at the cavity resonance is enhanced by 5-fold with respect to the cavities without the metal nanoparticle. The fluorescence is also compared before and after etching away the nanoparticle. Experimental quality factors and wavelength shifts are found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 30 publications
2
23
0
Order By: Relevance
“…54 with permission, subfigure n was reproduced from ref. 228 with permission, subfigure o was reproduced from ref. 56 with permission, and subfigure p was reproduced with permission.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…54 with permission, subfigure n was reproduced from ref. 228 with permission, subfigure o was reproduced from ref. 56 with permission, and subfigure p was reproduced with permission.…”
Section: Figmentioning
confidence: 99%
“…Periodic holes are fabricated on a column of a beam that is highly sensitive to refractive index changes. 228 (d) Bragg films. Multiple layers of thin films form a Bragg mirror, resulting in an approximately 100% reflection.…”
Section: Figmentioning
confidence: 99%
“…Since high dissipative losses and broad spectral features limit the performance of conventional metalbased plasmonic nanostructures in key applications, different strategies are currently pursued to mitigate these effects [16][17][18][19]. One promising approach seeks to integrate plasmonic nanostructures into a defined photonic environment where photonic and plasmonic modes can synergistically interact [20][21][22][23][24][25]. The coupling of localized surface plasmon resonances (LSPRs) with in-plane diffracted Rayleigh resonances to form surface lattice resonances (SLRs) in extended nanoparticle arrays is one example for this approach [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that Allsop et al [19] demonstrated S of 3365 nm∕RIU in surface plasmon resonance structure and Wang et al [33] demonstrated S of 900 nm∕RIU in slot double-beam waveguides; however, Q-factors are limited to 1000 in [19] and 700 in [33]. In order to overcome above drawbacks and realize simultaneously high Q and S, PhC nano-beam cavities (PCNCs) [34][35][36] are currently the subject of intense research interest because they possess a suite of attractive characteristics: high optical Q-factor, wavelength-scale effective mode volume, low effective mass, and small physical footprint. Integrated within planer photonic waveguide circuitry, PCNCs provide an ideal architecture for sensing applications.…”
Section: Introductionmentioning
confidence: 99%